2003
DOI: 10.1080/00365540310017096
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Severe CMV-colitis in an HIV Positive Patient Despite Moderate Immunodeficiency

Abstract: CMV-colitis is rare in HIV positive patients with CD4 counts higher than 100 microl(-1). We report a patient who was suffering from extensive CMV-colitis despite modest immune defect. The diagnosis was confirmed by repeated biopsies. The patient experienced an unusually long recovery which was only achieved after initiation of HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Cytomegalovirus (CMV) colitis is a common cause of lifethreatening opportunistic viral infection, especially in immunocompromised patients such as transplant recipients and HIV-infected patients. [1][2][3][4] Cytomegalovirus infections are generally asymptomatic in healthy adults, but CMV infection in immunocompromised host has very serious and fatal clinical outcomes. 5 Symptomatic CMV infection in immunocompetent patients has traditionally been considered to have a benign and self-limited course.…”
Section: Introductionmentioning
confidence: 99%
“…Cytomegalovirus (CMV) colitis is a common cause of lifethreatening opportunistic viral infection, especially in immunocompromised patients such as transplant recipients and HIV-infected patients. [1][2][3][4] Cytomegalovirus infections are generally asymptomatic in healthy adults, but CMV infection in immunocompromised host has very serious and fatal clinical outcomes. 5 Symptomatic CMV infection in immunocompetent patients has traditionally been considered to have a benign and self-limited course.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that immune reconstitution of specific T cell responses to a number of pathogens, including CMV, can occur following a HAART regimen [16, 17, 18, 19]. In a study by Deayton et al [16] on HIV patients, CMV DNA levels in the blood rapidly declined after the initiation of HAART.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few cases of CMV gastrointestinal disease reported in patients with CD4 counts greater than 50 cells/µL to 100 cells/µL (2,3). We describe a case of CMV colitis in an HIV-infected patient with a relatively preserved CD4 count.…”
Section: Cytomegalovirus Colitis In An Hiv-positive Woman With a Relamentioning
confidence: 96%
“…Two cases of HIV-infected patients with CMV colitis and relatively preserved CD4 counts in the setting of malnutrition and alcoholism have been described previously (2,3). Malnutrition has long been associated with anergy and impaired T cell function, thereby potentially predisposing patients to reactivation of CMV (4).…”
Section: Cytomegalovirus Colitis In An Hiv-positive Woman With a Relamentioning
confidence: 99%